Advantages of an Orychophragmus violaceus-maize rotation in reducing greenhouse gas emissions and reactive nitrogen losses and increasing net ecosystem economic benefits on the North China Plain. (1st October 2021) - Zhang, Zhenggui; An, Jie; Han, Yingchun; Feng, Lu; Li, Xiaofei; Xiong, Shiwu; Xing, Fangfang; Xin, Minghua; Li, Yabing; Wang, Zhanbiao
Abstract: Introducing cover crops into crop rotation systems is widely practiced to enhance the sustainability of agricultural production, but comprehensive evaluations of farmlands in cover crop-maize rotations on the North China Plain (NCP) from environmental, economic and net ecosystem economic benefits (NEEB) perspectives have rarely been performed. Therefore, a field experiment was conducted to compare economic benefits (EB), greenhouse gas (GHG) emissions, reactive nitrogen (Nr) losses, soil nutrient cycling values (SNV) and NEEB in three farming systems. The farming systems included a conventional wheat-maize (WM) rotation system, a government-promoted monoculture maize (MM) system and an innovative Orychophragmus violaceus ( O. violaceus )-maize (OvM) rotation system. The OvM rotation system achieved more EBs from the maize season but lower annual profits than the WM system, with 68.29% lower GHG emissions and 39.33% lower Nr losses. In addition, the highest SNV was achieved in the OvM rotation system, which was 700.18% and 116.97% higher than those in the WM and MM systems, respectively. Furthermore, the NEEB of the OvM rotation system was 61.92% and 29.31% higher than those of the WM and MM systems, respectively. In conclusion, the OvM rotation is recommended as a sustainable and cleaner maize production farming system for the NCP and other regions with similar ecological conditions because it led to lower annual GHG emissions and Nr losses, as well as higher SNV and NEEB than the other farming systems. Graphical abstract: Image 1 Highlights: Replacing wheat or fallow field with O. violaceus improved maize yield by 8%–12%. GHG emission of O. violaceus -maize was lower by 68% than those in wheat-maize. Nr loss was lower by 39% in O. violaceus -maize than those in wheat-maize. NEEB was increased by 62% in O. violaceus -maize relative to wheat-maize.